2017
DOI: 10.3389/fmicb.2017.00796
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic Comparison of Lophelia-Associated Bacterial Communities in the Western Atlantic Reveals Conserved Core Microbiome

Abstract: Over the last decade, publications on deep-sea corals have tripled. Most attention has been paid to Lophelia pertusa, a globally distributed scleractinian coral that creates critical three-dimensional habitat in the deep ocean. The bacterial community associated with L. pertusa has been previously described by a number of studies at sites in the Mediterranean Sea, Norwegian fjords, off Great Britain, and in the Gulf of Mexico (GOM). However, use of different methodologies prevents direct comparisons in most ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 83 publications
4
30
0
Order By: Relevance
“…The compositions of the microbiomes of our focal hosts, as measured by Bray–Curtis and Jaccard indices, do vary significantly across PtC, which is consistent with results from other marine invertebrates including corals (Lema et al ., ; Pantos et al ., ; Kellogg et al ., ) and some sponges (Burgsdorf et al ., ) analysed across various dispersal barriers or large geographic distances. In our case, such differentiation is largely driven by composition of rare taxa and changes in the relative abundance of dominant taxa at each site, as has been seen previously in oyster hemolymph microbiomes (Lokmer et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The compositions of the microbiomes of our focal hosts, as measured by Bray–Curtis and Jaccard indices, do vary significantly across PtC, which is consistent with results from other marine invertebrates including corals (Lema et al ., ; Pantos et al ., ; Kellogg et al ., ) and some sponges (Burgsdorf et al ., ) analysed across various dispersal barriers or large geographic distances. In our case, such differentiation is largely driven by composition of rare taxa and changes in the relative abundance of dominant taxa at each site, as has been seen previously in oyster hemolymph microbiomes (Lokmer et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Sequences with ≥97% identity were assigned to the same operational taxonomic unit (OTU), and each OTU was considered to represent a species. R software(V2.15.3, https://www.R-project.org) was used for statistical analysis and histogram construction based on the relative abundance of OTUs in the samples 29 . The raw data of JWY, 1-3 is deposited at NCBI SRA database under the project PRJNA601309.…”
Section: Methodsmentioning
confidence: 99%
“…Specific bacteria have already been identified such as Spirochetes or Endozoicomonas, which are observed in L. pertusa or M. oculata (Kellogg et al, 2009;Meistertzheim et al, 2016), and which may be crucial to the host physiology (Neave et al, 2016). It has also been demonstrated that L. pertusa and M. oculata have different species-specific microbial communities that can be maintained across different locations (Schöttner et al, 2012;Kellogg et al, 2017;Jensen et al, 2019). In addition, the bacterial community composition of L. pertusa can exhibit a strong temporal variability, but also differences within colonies, and between polyps from the same colony, contrary to the M. oculata microbiome, which appears much more stable (Meistertzheim et al, 2016;Galand et al, 2018).…”
Section: Introductionmentioning
confidence: 99%